2009
DOI: 10.1007/s10620-009-0840-2
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Orifice Inflammation in Ulcerative Colitis

Abstract: A 44-year-old man was diagnosed with distal ulcerative colitis (UC) when he had hematochezia at the age of 34. He had had a few relapses on maintenance oral mesalazine. He desired a total colonoscopy in the clinical remission. Physical examination showed no abnormalities and routine laboratory tests were normal. Colonoscopy disclosed the appendiceal orifice inflammation (AOI) with reddish and friable mucosa and mucopus (Fig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
3
4
0
Order By: Relevance
“…Moreover, a large cohort study found that combining proctitis and AOI features could improve UC diagnosis and facilitate physicians to identify this disorder among various conditions 16. Furthermore, the current study found that UC patients with AOI developed less severe disease than those without, as reflected by lower modified Mayo scores, and these findings were supported by previous reports 8 9. Skip lesions were previously thought only to be characteristic of Crohn’s disease.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, a large cohort study found that combining proctitis and AOI features could improve UC diagnosis and facilitate physicians to identify this disorder among various conditions 16. Furthermore, the current study found that UC patients with AOI developed less severe disease than those without, as reflected by lower modified Mayo scores, and these findings were supported by previous reports 8 9. Skip lesions were previously thought only to be characteristic of Crohn’s disease.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of AOI has been reported in UC patients, and its significance in UC has been investigated. However, the results are controversial 1 6–9 14–16. In this study, the significance of AOI in UC diagnosis and prognosis was prospectively studied.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Ulcerative colitis is a continuous disease, however, in rare cases skip lesions may be found scattered within the colon. The appendix may be involved in the process, particularly in the case of cecal involvement although ulcerative appendicitis may represent a skip lesion [10][11][12]. There is controversy whether appendicitis/appendectomy are protective against UC or might promote the disease [13].…”
mentioning
confidence: 99%